2014
DOI: 10.1037/a0031964
|View full text |Cite
|
Sign up to set email alerts
|

Trauma severity and control beliefs as predictors of posttraumatic growth among adolescent survivors of the Wenchuan earthquake.

Abstract: This study examined the relationships of trauma exposure and control beliefs with posttraumatic growth (PTG) in a sample of adolescent survivors of the Wenchuan earthquake (Time 1 n = 788, Time 2 n = 243). Results suggested that two aspects of exposure severity (indirect exposure and worry about others) had significantly positive associations with concurrently measured PTG, but only indirect exposure was significantly correlated with changes in PTG from Time 1 to Time 2. Primary and secondary control beliefs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 79 publications
(116 reference statements)
4
35
0
Order By: Relevance
“…The Trauma Exposure Questionnaire (Wu, Zhang, Lin, & Zang, ) is an 18‐item self‐report measure used to rate the trauma exposure experienced in the earthquake. One example is “The earthquake injured your relatives or friends.” According to previous research among Chinese adolescents, this scale has exhibited a good internal consistency (Wu et al, ; Ying et al, ). Each of the items is rated on a 3‐point scale of 3 ( saw it myself ), 2 ( heard about it from others ), and 1 ( did not experience any situations above ).…”
Section: Methodsmentioning
confidence: 91%
“…The Trauma Exposure Questionnaire (Wu, Zhang, Lin, & Zang, ) is an 18‐item self‐report measure used to rate the trauma exposure experienced in the earthquake. One example is “The earthquake injured your relatives or friends.” According to previous research among Chinese adolescents, this scale has exhibited a good internal consistency (Wu et al, ; Ying et al, ). Each of the items is rated on a 3‐point scale of 3 ( saw it myself ), 2 ( heard about it from others ), and 1 ( did not experience any situations above ).…”
Section: Methodsmentioning
confidence: 91%
“…Nevertheless, some positive outcomes, such as posttraumatic growth (PTG), have also been reported (Jin et al, 2014;Ying et al, 2014). PTG refers to positive changes, such as the feeling of strength and wisdom, placing increased value on friends and family, and finding a fresh appreciation for each new day, which results from experiencing a traumatic event Calhoun, 1995, 1996).…”
Section: Introductionmentioning
confidence: 95%
“…PTSD symptom levels were assessed at 18 months after earthquake by using the Child PTSD Symptom Scale (Foa et al, 2001) as applied to the Chinese population (Ying et al, 2014). This measure is a 17-item self-report scale that was designed to assess the occurrence and frequency of PTSD symptoms according to the diagnostic and statistical manual of mental disorders in relation to the most distressing event experienced by an individual.…”
Section: The Child Ptsd Symptom Scale (Cpss)mentioning
confidence: 99%
“…In this situation, people may resort to secondary control beliefs, which can contribute to adaptive outcomes by reducing emotional distress or facilitating disengagement from unattainable goals (Heckhausen et al, 2010). It has also been suggested that secondary control beliefs are related to less depression, less loneliness (Barlow et al, 2015; Compas et al, 2006), and more positive moods (Ying et al, 2014), which protects people from burnout. Thus, it is more likely that control beliefs can relieve burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Because control beliefs are an important personal characteristic or resource (Hobfoll, Johnson, Ennis, & Jackson, 2003), and PTSD itself indicates serious stress, we proposed in our study that control beliefs may buffer the relation between PTSD symptom severity and burnout. For example, compared to individuals with low primary control beliefs, individuals with high primary control beliefs may try to take an active approach toward change or the management of a stressful event (Ying et al, 2014), which in turn helps traumatized individuals change their focus from the negative aspects of trauma to positive ones (Nes & Segerstrom, 2006). Individuals with PTSD may also engage in positive behaviours, and thus the exacerbating role of PTSD in other negative consequences (e.g.…”
Section: Introductionmentioning
confidence: 99%